Fabrication of WO3nanofibers by high voltage electrospinning - Jarupat Sungpanich (2018)
Mixtures of 0.1, 0.3, and 0.5 mmol ammonium metatungstate hydrate (AMH), and poly (vinyl alcohol) (PVA) were electrospun by a + 20 kV direct voltage to synthesize fibers. Those of 0.5 mmol AMH were further calcined to have PVA removed and crystalline degree improved. At 500 °C and 2 h calcination, WO3nanofibers, including two main stretching modes, 3.24 eV direct energy gap, and 378 nm wavelength violet emission were detected. A possible formation mechanism of WO3nanofibers was proposed according to the experimental results. © 2011 Elsevier B.V. All Rights Reserved.